2013
DOI: 10.1371/journal.pone.0081409
|View full text |Cite
|
Sign up to set email alerts
|

Liver Accumulation of Plasmodium chabaudi-Infected Red Blood Cells and Modulation of Regulatory T Cell and Dendritic Cell Responses

Abstract: It is postulated that accumulation of malaria-infected Red Blood Cells (iRBCs) in the liver could be a parasitic escape mechanism against full destruction by the host immune system. Therefore, we evaluated the in vivo mechanism of this accumulation and its potential immunological consequences. A massive liver accumulation of P. c. chabaudi AS-iRBCs (Pc-iRBCs) was observed by intravital microscopy along with an over expression of ICAM-1 on day 7 of the infection, as measured by qRT-PCR. Phenotypic changes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 57 publications
0
16
0
1
Order By: Relevance
“…Infected erythrocytes are known to cytoadhere to small capillaries and post-capillary venules in host tissue, and this process is called sequestration [38,39]. Liver is one of organs in which iRBCs preferentially accumulate to avoid immune system surveillance inside the spleen, and iRBC sequestration within the liver endothelium is now emerging as another factor that promotes liver damage [40][41][42]. Several studies suggest that iRBC sequestration contributes to the intrahepatic obstruction of blood flow, which leads to hepatocellular hypoxia and excessive intravascular hemolysis, causing increased oxidative stress and leukocyte infiltration [40,[43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infected erythrocytes are known to cytoadhere to small capillaries and post-capillary venules in host tissue, and this process is called sequestration [38,39]. Liver is one of organs in which iRBCs preferentially accumulate to avoid immune system surveillance inside the spleen, and iRBC sequestration within the liver endothelium is now emerging as another factor that promotes liver damage [40][41][42]. Several studies suggest that iRBC sequestration contributes to the intrahepatic obstruction of blood flow, which leads to hepatocellular hypoxia and excessive intravascular hemolysis, causing increased oxidative stress and leukocyte infiltration [40,[43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Liver is one of organs in which iRBCs preferentially accumulate to avoid immune system surveillance inside the spleen, and iRBC sequestration within the liver endothelium is now emerging as another factor that promotes liver damage [40][41][42]. Several studies suggest that iRBC sequestration contributes to the intrahepatic obstruction of blood flow, which leads to hepatocellular hypoxia and excessive intravascular hemolysis, causing increased oxidative stress and leukocyte infiltration [40,[43][44][45]. Infiltrated leukocytes also produce inflammatory mediators, thereby enhancing hepatic inflammation [43,46].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that PcAS infection can enhance Foxp3 ϩ regulatory T-cell (Treg) responses in peripheral tissues, such as the liver (24). Therefore, it is at least theoretically possible that PcAS coinfection also boosts Treg responses in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Early-stage infection IL-10 synthesis can also involve the neutrophils, because inhibition of IL-10 signaling abrogated the increase in Leshmania parasite loads in BALB/c mice during the first week [89]. Apart from acute phase infections, the IL-10 involvement during the first week is observed even in intracellular pathogens, tumors, and transplants, which demonstrate implication of PMCs, NK, and CD4+ T cells in the IL-10 synthesis [130,156,158,165,166]. Increased IL-10 production by CD4CD25FoxP3+ T cells along few weeks was observed in a time-dependent manner during melanoma tumor growth in mice, while the initial association of IL-10 production with migration of macrophages, DCs, and neutrophils following peritoneal scaffold implantation was replaced by association with T lymphocytes that became prevalent by day 14 [124,142].…”
Section: Il-10-an Indicator and Time-dependent Effector Of Immunity Smentioning
confidence: 96%